Analysis of Audiometric Differences of Patients with and without Tinnitus in a Large Clinical Database - Gollnast, Dominik; Tziridis, Konstantin; Krauss, Patrick; Schilling, Achim; Hoppe, Ulrich; Schulze, Holger (Frontiers in Neurology, 2017)
Human hearing loss (HL) and comorbidities like tinnitus pose serious problems for people’s daily life which in most severe cases may lead to social isolation, depression and suicide. Here we investigate the relationship between hearing deficits and tinnitus. To this end we conducted a retrospective study on anonymized pure tone and speech audiometric data from patients of the ENT hospital Erlangen in which we compare audiometric data between patients with and without tinnitus. Overall data from 37661 patients with sensorineural (SHL) or conductive hearing loss (CHL) with (T, 9.5%) or without (NT, 90.5%) a tinnitus percept in different age groups and with different tinnitus pitches were included in this study. The results of the pure tone audiometry comparisons showed significant differences in T patients compared to NT patients. In young patients, we generally found lower hearing thresholds in T compared to NT patients. In adult patients, differences were more heterogeneous: hearing thresholds in T patients were lower in low frequency ranges, while they were higher at high frequencies. Furthermore, lower thresholds were more often found in CHL patients and could rarely be detected in SHL patients. In speech audiometry only CHL patients with high pitched tinnitus showed lower thresholds compared to NT patients’ thresholds. The results of this study may point to a biologically plausible functional benefit on hearing thresholds in HL tinnitus patients. We hypothesize that the physiological mechanism of stochastic resonance counteracts HL by adding neuronal noise to the system. This neuronal noise may induce changes in the auditory pathway and finally – as a side effect of threshold improvement – lead to the development of a tinnitus percept. We propose a general model of changed hearing thresholds in T patients, being either decreased or increased compared to NT patients.